BERMAIN TUMBLE TOWER (JENGA) MODIFIKASI TERHADAP PERILAKU SELF STIMULATION ANAK AUTIS DI SEKOLAH DASAR NEGERI - Apfrensisca, (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: Children with autism experience obstacles in behavior, one of which is the behavior of self-simulation, this behavior can disrupt the people around him. The purpose of this study is to prove whether the behavior of self-stimulation in children with autism can be reduced by playing tumble tower (jenga) modification. This type of research is a single subject research (SSR) with A-B-A design. Data collection techniques used are observation and documentation. Data analysis technique used is visual analysis in condition and visual analysis between condition. The results showed that the activity of tumble tower (jenga) play modification can reduce the behavior of self-stimulation (holding friend’s hair) in children with autism that was done 3-13 times with total duration 36-139 then reduced to 0-1 times with duration 5-16 Seconds. Keywords: Playing tumble tower, Jenga, Self stimulation